Curso técnico em enfermagem integrado ao ensino médio: caracterização e trajetória profissionais dos egressos, por meio da utilização de redes sociais - Santiago, Luciana Maria Montenegro (2014)
The Politics of the Integrated Technical Education Secondary Level – EMI (Decree no. 5.154/2004) is a policy of human resource training proposed by the Ministry of Education (MEC), which has invested heavily in the expansion of federal and state networks of professional and technological education in Brazil. The Technical College of Nursing was one of the pioneers offered, the State of Ceará, the end of 2013, contributed to the training of approximately 6,000 professionals. The this study's objective was to characterize the career of the graduates of nursing technical course coming from the Integrated Secondary School in Sobral, in Santa Quitéria and In Camocim - Ceará / Brazil, through the use of a social network - Facebook. This is a case study conducted in the years 2012-2014. The locations of the research were Camocim CE / EC State Schools Professional Education Integrated Education located in Sobral / CE, Santa Quitéria / tendered and Technical College of Nursing, and the subjects were 150 graduates of these schools during 2011 and 2012, 60.7 %% the total. For components, was sent up an online form via facebook with questions that contemplated the study goals, which referred to the Committee on Ethics in Research (CEP) the Universidade Estadual Vale do Acaraú – UVA was approved by ordinance no. 384.443/13. About socioeconomic identification, predominated females (78%) aged between 20 and 21 years (32%), single (92%) residing with her parents (83%), with an income of two minimum wages (48%). On political participation, 96% know the Code of Ethics, however not follow political movements of the profession (54%). Entities were recognized nursing COFEN / Coren (33%) and ABEn (11%). About professional development, 43% presented, highlighting the internet (35%) and classroom courses (20%) as a modality of choice. The few time, lack motivation and lack encouragement were the reasons for not conducting. Regarding vocational training, 41% are doing graduation, and of these, 70% in private institutions, and the health the most sought after (84%), specifically the nursing program (50%). The graduates working in the area corresponding to 54%, with a schedule of 42h weekly, CLT (44%) in non-profit hospitals (39%) or social organizations (35%) during daytime (64%). The occurrence of employed graduates in primary care was very low (3%). Knowing the formation process of the graduates of the State Schools of Vocational, we concluded that this policy has failed to achieve its goal of enabling these students to enter the world of work and the pursuit of progressive training in the chosen area of expertise. However, one notes the fact of Primary Care does not configure as a field of action sought by the subjects, making us think about the way education policies of Human Resources for the NHS can help change this scenario. Also noteworthy is that the use of social networks in the pursuit of research subjects was a very important tool. Therefore, it is suggested that further studies on the composition curriculum are made.